The Relationship Between The Intensity of Watching Korean Dramas With The Attitude Of Academic Procrastination Of UIN Jakarta Students In Era Of The Pandemic - Arini Bunga Firdaus; Salastia Paramita Nurhuda; Wahyunengsih Wahyunengsih (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
This study is an initial study to determine and analyze the relationship between the intensity of watching Korean dramas and the academic procrastination attitude of UIN Jakarta students during the Covid-19 pandemic. The object of this research is the relationship between the intensity of watching Korean dramas and the attitude of academic procrastination. In the research instrument, researchers use Google Forms or online questionnaires. The method used by the researcher is descriptive quantitative method with correlational technique. The subjects in this study were UIN Jakarta students from various faculties and majors, but the researchers used a random sampling technique, which was taken as many as 30 students. In processing the data using Microsoft Excel 2019 using the correlation formula. The results in the study show a correlation coefficient of r = 0.1232 with a significance of p = 0.000 (p < 0.01) so the conclusion of this study shows that there is no positive and significant relationship between the intensity of watching Korean dramas and the academic procrastination attitude of UIN Jakarta students in the era of the Covid-19 pandemic. Or it can be said that there is also a very weak correlation between the intensity of watching Korean dramas and the attitude of academic procrastination UIN Jakarta students in the Covid-19 pandemic era. Because most UIN Jakarta students watch Korean dramas only for refreshing from the fatigue of the existing tasks, after that students immediately return to their college assignments without delaying for long.